2021
DOI: 10.21203/rs.3.rs-151449/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Relationship Between Satisfaction With Mental Health Services, Personal Recovery and Quality of Life Among Service Users With Psychosis: A Cross-Sectional Study

Abstract: Background: Mental health policy internationally emphasizes patient centredness and personal recovery. This study investigated the relationship between satisfaction with mental health services among service users with psychosis in Norway, and personal recovery, perceived support for personal recovery, and quality of life.Methods: Cross-sectional data were collected from 292 service users diagnosed with psychosis from 39 clinical sites across Norway. Satisfaction with services was assessed using the Client Sati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Moreover, service users who evaluated the support they receive by their healthcare provider as valuable and who reported to have a meaningful relationship with them had a lower degree of functional limitation. The degree of functional limitations (measured with WHODAS 2.0) in the sample was comparable with other study populations with severe mental illness (44,53). In this study, participants indicated the highest degree of functional limitation in the domains participation in society, work, and household, followed by getting along with people.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…Moreover, service users who evaluated the support they receive by their healthcare provider as valuable and who reported to have a meaningful relationship with them had a lower degree of functional limitation. The degree of functional limitations (measured with WHODAS 2.0) in the sample was comparable with other study populations with severe mental illness (44,53). In this study, participants indicated the highest degree of functional limitation in the domains participation in society, work, and household, followed by getting along with people.…”
Section: Discussionsupporting
confidence: 80%
“…Our study showed that service users across sites were generally satisfied with the support received from their mental health care providers. A recent study from Norway which also used the INSPIRE tool found that service users who experienced higher perceived support for personal recovery from their health care provider are more satisfied with the care they receive (53). Nevertheless, there is room for improvement across all centers of the project.…”
Section: Discussionmentioning
confidence: 99%
“…The validation of a Norwegian translation of the CSQ-8 is particularly timely. First, over the last few years, it has increasingly been used as a measure of patient satisfaction [14,15,[34][35][36][37][38][39][40][41][42][43]. Second, several registered trials plan to use the questionnaire as an outcome measure [44][45][46][47][48].…”
Section: Introductionmentioning
confidence: 99%